Children’s Rights under Threat: Reflection from Emergencies Situation in Indonesia - Widiastuti, Dini (Yayasan Jurnal Perempuan, 2020)
In time of emergency, gender based and sexual violence are common occurrence, including in the form of child marriage; schooling is disrupted for a considerable period of time and children are falling behind in their education and they have less opportunity to be together and play with their friends; plus, sexual and reproductive health are not normally receiving adequate attention. Participation of children and adolescents, boys and girls, is not only a matter of fulfillment of child rights but is in fact central for the success of humanitarian response. This writing attempts to analyse the impact of disaster on the fulfillment of child rights, especially the rights to protection and free from violence, education, health, play and participation and be heard, by using the UN Convention on the Rights of the Child as the framework. Gender, inequality and vulnerability lens are used as analytical tools. The method used is literature study, whilst the data and learning from the two major disasters in Indonesia occurred in 2018, the earthquake in Lombok, West Nusa Tenggara province and earthquake, tsunami & liquefaction in Central Sulawesi province are used as the main materials for analysis.